The genetic relationship between hypotension and delirium: a Mendelian randomization study - Wang, Chengli; Wu, Jiayao; Lin, Yiqing; Liu, Zhongqi; Liufu, Ning; Cao, Minghui (Frontiers in Neurology, 2024)
Background Observational research suggests that hypotension is a potential hazard factor of delirium. Nevertheless, previous observational articles are limited in their ability to establish causality between hypotension and delirium. The present study was sought to explore the genetic causal relationship between these two conditions using two-sample Mendelian randomization (MR). Methods Genome-wide association study (GWAS) summarized data for hypotension and delirium were obtained from the FinnGen Consortium. The researchers utilized several statistical methods, such as inverse-variance weighted (IVW), weighted median, MR Egger, weighted mode, and simple mode in conducting the MR statistical analysis. In order to identify heterogeneity among the MR outcomes, we employed the Cochrane’s Q test. Furthermore, we used the MR-Egger intercept test and MR pleiotropy residual sum and outliers (MR-PRESSO) test to examine horizontal pleiotropy. Results The findings revealed that hypotension was identified as an independent hazard variable for delirium (p = 0.010, odds ratio [OR] [95% confidence interval (CI)] = 1.302 [1.066–1.592]) using the IVW method. The presence of horizontal pleiotropy was found to have minimal impact on establishing causal relationship (p = 0.999), and there was no evidence to suggest heterogeneity between genetic variations (p = 0.379). Additionally, the leave-one-out method demonstrated the stability and robustness of this association. Conclusion We performed two-sample MR analyses and found evidence of a genetic causal relationship between hypotension and delirium. Our findings suggest that individuals with a genetic predisposition for hypotension may have a higher risk of developing delirium. This suggests that interventions aimed at improving perioperative hypotension could aid in limiting the incidence of delirium.